Intra-hospital mortality and morbidity and six-month follow up of patients with myocardial infarction - Babapour, Behzad; Sadeghieh-Ahari, Saeid; Panahi, Saba (International Journal of Research in Medical Sciences, 2022)
Background: Cardiovascular disease is one of the leading causes of disability and premature death worldwide. Adjustment of risk factors has been shown to reduce morbidity and mortality in people with diagnosed or even undiagnosed cardiovascular disease. In this study, we examined mortality and morbidity over a six-month period among patients with MI. Methods: This cross-sectional study was done on 322 patients admitted to Imam Khomeini Hospital in Ardabil during September 2020 to February 2020 with the diagnosis of acute myocardial infarction and their mortality and morbidity rates and their relationship with age, gender, risk factors (diabetes, hypertension, family history) and the type of treatment performed. The data of all patients will be collected in special forms and will be analyzed using SPSS software. Results: Of all patients, 27 died, all of whom were older (over 59 years), and about 125 had morbidity during 6 months, the majority (78%) being older. In terms of gender, mortality and morbidity rates were lower in men than in women. Risk factors lie diabetes, hypertension and positive family history had a significant impact on mortality and morbidity at first glance and findings showed that streptokinase injection was superior to primary coronary intervention with mortality and morbidity. Conclusions: Findings showed that mortality and morbidity rate in acute myocardial infarction was directly related to the type of treatment (primary coronary intervention versus streptokinase injection), age, sex, being diabetic, having hypertension and having a positive family history.